In Vitro Effect of Temperature on Dentin Bond Strength of Universal Adhesive Systems - Akarsu DDS, PhD, Serdar (2019)
The aim of this study was to evaluate the shear bond strength (SBS) of two universal adhesives (Universal Single Bond and All Bond Universal) and a two-step self-etch adhesive system (Clearfil SE Bond) to dentine at various temperatures. Materials and Methods: One hundred and twenty dentin specimens were divided randomly to 12 groups, according to adhesive systems (Universal Single Bond and All Bond Universal, Clearfil SE Bond)  and temperature  ( 4ºC, 20 ºC, 36ºC, 55ºC) used. Dentin specimens were prepared (n :10, adhesives were applied, and composite cylinders were polymerized. Statistical analysis of the SBS data was performed using Two-way analysis of variance (ANOVA) and Tukey’s Honestly Significant Differences post-hoc test. Results: The Clearfil SE Bond was shown to have higher SBS than the universal adhesives at all temperatures; however, there was no statistically significant difference (P>0.05). In both groups, the lowest SBS values were observed in the samples at 4°C while the highest SBS values were observed in the samples at 55°C. In this case, there was a statistically significant difference (P<0.05). Conclusions: The results suggest that the effectiveness of an adhesive may increase if it is preheated at 36°C or above before use instead of being used immediately after removal from the refrigerator or at room temperature.